What factors affect small and medium-sized enterprise's ability to borrow from bank: Evidence from Chengdu City, capital of South-Western China's Sichuan province - Hongjiang Zhao; Wenxu Wu; Xuehua Chen (Fachhochschule für Wirtschaft Berlin, Business Institute Berlin, 2006)
There are many factors that affect SMEs' ability to borrow from bank. Based on facts and data about SMEs' financing in Chengdu city, capital of Southwestern China's Sichuan province, this paper is intended to investigate the factors affecting SMEs to borrow from bank by methods of empirical study. We find that whether SMEs can provide collateral or guarantee is a decisive factor, factors such as firm size, willingness to accept bank's clauses, close relationship with bank play an important role. But in contrast to intuition, correlation analysis and regression result shows that SMEs' financial variables such as income, net profit, asset-debt ratio and credit score is not obvious to affect their ability to get bank loan. Consistent with theory prediction and qualitative analysis, firm size is the most important factor to affect SMEs' ability to borrow from bank. The regression results reflect information asymmetry between SMEs and banks, and that banks had taken a simple way to protect themselves.
Keywords: 330; small and medium-sized enterprise (SME); ability to borrow; firm size; logit model; China's Sichuan Province